Simulation Model of Groundwater within Umm-Er Radhuma Formation in Anbar Province / Western Iraq - A. Hussain, Tariq (Iraqi Journal of Science, 2023)
The study area is located in the south-eastern part of AL- Anbar province, between latitudes (31˚02ˉ00˭ -33˚03ˉ00˭) north and longitudes (40˚02ˉ00˭ -43˚04ˉ00˭) to the east. The research studied predictive mathematical Model of groundwater within Umm-Er Radhuma Formation and by (44) wells distributed randomly within the boundaries of the study area, all of them fall within the unconfined aquifer. Through the operating of wells on the time of (30) day and taking the operating results of each (5) days, results showed that the drawdown in groundwater levels values ranged from (13) cm after running the model for a period of 5 days and (120) cm after running Model for thirty days. And the drawdown values are concentrated near wells sites and the drawdown decline as we move away from the sites of these wells and this reflects the nature of the water reservoir located in the study area, which is characterized by high production where compensation resulting from the operation of the wells decline rapidly by the reservoir. Therefore the values of the drawdown in elevations appeared very low. The study also showed the possibility of drilling additional wells in this area depending on this model to benefit from them in the future for different uses.